(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
This work was carried out in the Experimental Farm "La María" of the State Technical University of Quevedo (UTEQ) with the objective of characterizing and georeferencing the physical properties of the Eutric Fluvisols soils for agricultural use in the farm "La María". Where there is a lack of knowledge of the physical characteristics, inadequate management and use of soils being necessary the use of technologies such as geographic information systems (GIS) that allow storing, analyzing and managing activities of the different sites of agricultural interest. This research was conducted from June to October 2018, using a completely randomized design (CRD) with 20 treatments considered by horizons and surfaces in 3 replications. The data were analyzed in the statistical program InfoStat free version (VL), and subjected to Tukey’s test at 95% probability. These results were plotted on a georeferenced map in a GIS (ARGIS) (VL), WGS 1984 UTM Zone 17S coordinate system. The soils of the "La María" farm had an average bulk density of 1.18 g/cm3 and real density of 2.24 g/cm3. There was a pore space percentage of 46%, average moisture percentage of 41%, and soil aggregate size of 4.28 mm. In the texture analysis, 85% of the soils of the farm have a loamy soil texture.